Firm-level Responses to Government Regulation: Theoretical and Research Approaches - Shaffer, Brian (Journal of Management, 1995)
Historically, the relationship between business firms and government has usually been approached in terms of its effects on the process of representative democracy (i.e., the implications of business political activity for the functioning of government). More recently, perspectives on business-government relations have developed within a managerial framework [i.e., from the viewpoint of the corporation and the manager]. This article discusses the consequences of public policies for the competitive environment of the firm, which provides one explanation for political behavior. Firm-level responses include both strategic adaptation and attempts to influence public policy. It discusses a variety of research approaches to understanding the firm S strategic use of public policy processes, as well as suggestions for further research.